Kemampuan Pseudomonas Kelompok fluorescens dan Bacillus spp. Menghambat Perkembangan Fusarium spp. Penyebab Penyakit Layu Tanaman Terung - Abdullah Syukur; Noor Aidawati; Helda Orbani Rosa (JURNAL PROTEKSI TANAMAN TROPIKA, 2022)
Eggplant (Solanum melongena L.) The demand for eggplant was increasing, but the availability of eggplant is low so it cannot be fulfilled. One of the causes of low eggplant production is due to the attack of wilt disease on eggplant plants caused by Fusarium oxysporum. Symptoms include wilted leaves, yellowing leaves and brown root and stem tissue. Control that is often done is to use pesticides (fungicides) which can cause environmental pollution. One control of Fusarium spp. wilt disease. with microbial antagonists. This research was conducted to determine the ability of isolates of rhizobacteria Pseudomonas fluorescens group (PF) and Bacillus spp. from bamboo, chili and ferns inhibited the growth of Fusarium spp. in vitro. Completely Randomized Design (CRD) with isolates of Pseudomonas fluorescens group and Bacillus spp. each 4 treatments, control. Testing the inhibitory power of isolates of Pseudomonas fluorescens group and Bacillus spp. carried out by the challenge method and in vitro. Observations were made on the percentage of inhibition of rhizosphere bacteria (DH) after incubation for 7 days. All isolates of Pseudomonas fluorescens group and isolates of Bacillus spp. Has different inhibitory power on the fungus Fusarium spp. The isolates of Pseudomonas fluorescens group derived from bamboo roots from the Palem area (KPBP) (81.95%) were isolates that had the highest percentage of inhibition and Bacillus spp. derived from chili roots from the Guntung Manggis area (BGTP1) (70%) was the isolate that had the highest percentage of inhibition.